Ancient Egypt Hieroglyphs — Contemporary Reading for Fresh Ideas in Art - Весна Монд-Козловська (Культура і мистецтво у сучасному світі, 2023)
The aim of this article is to rationalise emotional, intellectual and aesthetic impact of Egyptian hieroglyphs through their examination with the research tools of the aesthetics as an academic discipline and its related sciences. Their evocative power made them possess the property of life, resulting in attributing the ancient Egyptian writing with the power of storing a universal sagacity. The latter is suggested as both a rationale and an outcome of every creative process to which the art of hieroglyphs seems to invite. Results. Nevertheless, through taking a down-to-earth stand for a methodological choice we aim to be reconnected with techniques of making a single hieroglyph and getting insight into conceptual principles of tying them in rows of a text that generate intentional ancient meaning to be decoded and delighted through present day lens. Scientific novelty. The study tries to establish a new both bond and relationship between the signifier and the signified to allow contemporary reading of the ancient signs that could bridge modern man with their Ancient Egypt ancestors. Following Ferdinand de Saussure’s exposition of the semiotic nature of the symbolisation process it opens an investigation into ways the modern mind can bear new meaning that will substitute the extinct signified in relation to the compelling ancient signifier a single hieroglyph is. Conclusions. Adhering to a formal scrutiny of the outer form of an ideogram in the first place, we intend to both challenge and inform contemporary art with strongly symbolic nature of ancient Egypt thought and spirituality that yielded those polysemous signs created with extremely sublime logic of artistic wisdom and craft. A nonrandom and revealing interchange between logics and aesthetics suggests the given art form can bring to light some strict and invariant rational laws that constituted it.